The harvest and the reapers : oral traditions of Kentucky - Clarke, Kenneth W.; Clarke, Mary Washington (Kentucky Bicentennial bookshelf., 1974)
The oral tradition of Kentucky is one of the most rich and interesting in the nation and has attracted a number of outstanding men and women -- scholars and writers, teachers and singers -- who have devoted their energies to Kentucky's folk and their ways. Some have collected examples of the state's unique speech patterns and word usages. Others have recorded local place names and the legends that surround them, or the yarns and tall tales transmitted from one generation to the next. Musicians have sought the authentic mountain folk songs, both old and new, and gifted writers have woven detail.